Cardiovascular safety of oral semaglutide in patients with type 2 diabetes: Rationale, design and patient baseline characteristics for the PIONEER 6 trial. Issue 3 (11th November 2018) - Bain, Stephen C.; Mosenzon, Ofri; Arechavaleta, Rosario; Bogdański, Pawel; Comlekci, Abdurrahman; Consoli, Agostino; Deerochanawong, Chaicharn; Dungan, Kathleen; Faingold, Maria C.; Farkouh, Michael E.; Franco, Denise R.; Gram, Jeppe; et al.
Abstract : Aims: To assess the cardiovascular (CV) safety of oral semaglutide, the first tablet formulation of a glucagon‐like peptide‐1 receptor agonist. Materials and methods: PIONEER 6 is a multinational, randomized, placebo‐controlled, double‐blind trial in patients with type 2 diabetes at high risk of CV events (defined as being aged ≥50 years and having established CV disease [CVD] or moderate [stage 3] chronic kidney disease [CKD], or being aged ≥60 years with ≥1 other CV risk factor). Patients were randomized to once‐daily oral semaglutide (up to 14 mg) or placebo added to standard of care. The primary composite endpoint is time to first occurrence of CV death or non‐fatal myocardial infarction or non‐fatal stroke. The primary hypothesis was to exclude an excess in CV risk with oral semaglutide by assessing non‐inferiority versus placebo for the primary endpoint (non‐inferiority margin of 1.8 for the upper boundary of the 95% confidence interval of the hazard ratio). PIONEER 6 is event‐driven, with follow‐up continuing until accrual of at least 122 primary outcome events. There is no pre‐defined minimal duration. Results: Overall, 3183 patients have been enrolled (mean age 66.1 years, 31.6% females) in 214 sites across 21 countries. At baseline, the mean duration of diabetes was 14.9 years, mean glycated haemoglobin concentration was 66 mmol/mol (8.2%), and 84.6% of patients had established CVD/moderate CKD. Conclusions: PIONEER 6 will provide evidence regarding the CV safety of oral semaglutide in patients with type 2 diabetes and high CV risk.